Maternal docosahexaenoic acid supplementation during lactation improves exercise performance, enhances intestinal glucose absorption and modulates gut microbiota in weaning offspring mice - Lu, Dalu; Yao, Die; Hu, Gaoli; Zhou, Jiefei; Shen, Xiuhua; Qian, Linxi (Frontiers in Nutrition, 2024)
Introduction：Intestinal dysfunction induced by weaning stress is common during breastfeeding period. Docosahexaenoic acid (DHA) is well known for promoting visual and brain development, but its effects on early intestinal development remain unknown. This study investigated the impact of maternal DHA supplementation during lactation on intestinal glucose absorption and gut microbiota in weaning offspring mice. Materials and methods：Dams were supplemented with vehicle (control), 150 mg/(kg body weight · day) DHA (L-DHA), or 450 mg/(kg body weight · day) DHA (H-DHA) throughout lactation by oral administration. After weaning, pups were randomly divided into three groups for athletic analysis, microbial and proteomic analysis, biochemical analysis, 4-deoxy-4-fluoro-D-glucose (4-FDG) absorption test, and gene expression quantitation of glucose transport-associated proteins and mTOR signaling components. Results：The H-DHA group exhibited enhanced grip strength and prolonged swimming duration compared to the control group. Additionally, there were significant increases in jejunal and ileal villus height, and expanded surface area of jejunal villi in the H-DHA group. Microbial analyses revealed that maternal DHA intake increased the abundance of beneficial gut bacteria and promoted metabolic pathways linked to carbohydrate and energy metabolism. Proteomic studies indicated an increased abundance of nutrient transport proteins and enrichment of pathways involved in absorption and digestion in the H-DHA group. This group also showed higher concentrations of glucose in the jejunum and ileum, as well as elevated glycogen levels in the liver and muscles, in contrast to lower glucose levels in the intestinal contents and feces compared to the control group. The 4-FDG absorption test showed more efficient absorption after oral 4-FDG gavage in the H-DHA group. Moreover, the expressions of glucose transport-associated proteins, GLUT2 and SGLT1, and the activation of mTOR pathway were enhanced in the H-DHA group compared to the control group. The L-DHA group also showed similar but less pronounced improvements in these aspects relative to the H-DHA group. Conclusions：Our findings suggested that maternal DHA supplementation during lactation improves the exercise performance, enhances the intestinal glucose absorption by increasing the expressions of glucose transporters, and beneficially alters the structure of gut microbiome in weaning offspring mice.